Isolation, sequencing and overexpression of the gene encoding the theta subunit of DNA polymerase III holoenzyme. - Carter, J R (1993)
The gene encoding the theta subunit of DNA polymerase III holoenzyme, designated holE, was isolated using a strategy in which peptide sequence was used to derive a DNA hybridization probe. Sequencing of the gene, which maps to 41.43 centisomes of the chromosome, revealed a 76-codon open reading frame predicted to produce a protein of 8,846 Da. When placed in a tac promoter expression vector, the open reading frame directed expression of a protein, that comigrated with authentic theta subunit from purified holoenzyme, to 6% of total soluble protein.